Synthesis and Characterization of β-Ga2O3/por-GaAs/mono-GaAs Heterostructures for Enhanced Portable Solar Cells - Suchikova, Yana; Kovachov, Serhii; Bohdanov, Ihor; Drozhcha, Dariya; Kosogov, Ivan; Karipbayev, Zhakyp T.; Popov, Anatoli I. (Precarpathian National University, 2024)
This study comprehensively details the successful synthesis of a β-Ga2O3/por-GaAs/mono-GaAs heterostructure designed for portable solar cells. Employing a combination of electrochemical etching and high-temperature oxygen annealing, we engineered a heterostructure that exhibits both crystalline and amorphous phases. XRD, SEM, and Raman spectroscopy analyses confirmed the formation of crystalline β-Ga2O3 and GaAs, with the porosity in the GaAs layer enhancing light absorption and charge collection. The potential of the heterostructure to improve photovoltaic performance is attributed to the inherent stability of Ga2O3 and the increased surface area provided by the porous GaAs. © 2024 Precarpathian National University. All rights reserved. This is an open-access publication Suchikova Y., Kovachov S., Bohdanov I., Drozhcha D., Kosogov I., Karipbayev Z.T., Popov A.I. Synthesis and Characterization of β-Ga2O3/por-GaAs/mono-GaAs Heterostructures for Enhanced Portable Solar Cells [Синтез та характеристика β-Ga2O3/por-GaAs/mono-GaAs гетероструктур для покращених портативних сонячних елементів] (2024) Physics and Chemistry of Solid State, 25 (3), pp. 546 - 552, DOI: 10.15330/pcss.25.3.546-552.
The National Research Foundation of Ukraine has supported the study via Project No. 0124U000223 \u201CDesign and research of oxide heterostructures for portable solar cells\u201D. In addition, the research has been partly supported by COST Action CA20129 \u201CMultiscale irradiation and chemistry driven processes and related technologies\u201D (MultiChem). Institute of Solid State Physics, University of Latvia, ISSP UL as the Center of Excellence, is supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; electrochemical etching; heterostructure; mono-GaAs; oxygen annealing; por-GaAs; Raman spectroscopy; SEM; solar cells; XRD; β-Ga2O3